Analysis of the variation in the stiffness modulus through four-point bending tests - Pais, Jorge C. (2009)
Pavement layers are characterized by basic material properties, among which the stiffness modulus and the Poisson ratio assume a preponderant importance in linear elastic anal-ysis. The stiffness modulus is usually assessed through samples extracted from a pavement or prepared in laboratory. The number of specimens used to calculate the stiffness modulus of an asphalt mixture plays an important role in the precision of pavement design. Thus, this paper presents a study to evaluate the number of tests to assess the stiffness modulus of asphalt mix-tures through the four-point bending technique. The results obtained from five different asphalt mixtures were used to evaluate the stiffness dispersion to define the number of tests. A separate study conducted to define the variation of the stiffness modulus allowed to ensure a certain pre-cision in pavement design. This analysis was made for several pavement structures in which the asphalt layer thickness and the subgrade stiffness varied among the samples.